Analysis of the influence of baffles and shields on the cooling of a digital transmission equipment - Ramos, R. A V [UNESP]; Milanez, L. F. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 1996)
In this work design criteria for cooling of electronic systems used in a digital transmission equipment are considered. An experimental study using a simulated electronic equipment in which vertically oriented circuit boards are aligned to form vertical channels is carried out. Resistors are used to simulate actual components. The temperature of several components in the printed circuit boards are measured and the influence of the baffles and shields on the cooling effect are discussed. It was observed that the use of the baffles reduce the temperature levels and, the use of shields, although protecting the components from magnetic effects, cause an increase in the temperature levels.
Keywords: Cooling; Digital communication systems; Electronics packaging; Heat shielding; Magnetic field effects; Thermal effects; Digital transmission equipment; Printed circuit design